1997
DOI: 10.1111/j.1432-1033.1997.0468a.x
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Truncated Forms of the Elongation Factor 1α from the Archaeon Sulfolobus solfataricus

Abstract: Two truncated forms of the Sulfolohus solfuturicus elongation factor 1 a (SsEF-la), corresponding to the putative domains G+M, Ss(GM)EF-la, and G, Ss(G)EF-la, have been constructed by gene engineering, produced in Escherichin coli and purified. Neither truncated form was able to sustain poly(Phe) synthesis but they were able to bind guanine nucleotides with an affinity much higher with respect to that of the intact factor. However, the difference in the affinity for GDP and GTP became progressively reduced wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
19
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 20 publications
5
19
1
Order By: Relevance
“…The G‐domains set up a “basic level” of the thermal stability of the EF‐Tus (cf. also Sanangelantoni et al 1996; Masullo et al 1997). The level set up by the thermophilic BstG‐domain was ∼20°C higher than that of the EcG‐domain.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The G‐domains set up a “basic level” of the thermal stability of the EF‐Tus (cf. also Sanangelantoni et al 1996; Masullo et al 1997). The level set up by the thermophilic BstG‐domain was ∼20°C higher than that of the EcG‐domain.…”
Section: Discussionmentioning
confidence: 92%
“…Nock et al (1995) reported that in Thermus thermophilus EF‐Tu, the deletion of domains 2/3 or only of domain 3 provoked a lower affinity for guanine nucleotides similarly as in the E. coli system. In contrast, the same truncation of Sulfolobus solfataricus EF‐1α increased the affinity for GDP and GTP by about one order of magnitude compared with the intact protein (Masullo et al 1997). This implies that the same level of affinity to guanine nucleotides can be attained by different strategies in different EF‐Tus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The EF-Tu of E. coli and EF-1α of S. solfataricus are of similar structure, both triangular three-domain proteins with a hole in the middle and substantial differences between the reactant GTP (active) and product GDP (inactive) state. Despite the role of interdomain interactions ensuring long-range communication, some essential features of the EF activity can be investigated by considering only the catalytic domain, as the isolated domain is catalytically active. , The catalytic subunit is slightly less thermostable than the three-domain protein for both the mesophile and the thermophile. The inactivation temperature of the catalytic subunit in the EF-Tu is 41 °C as opposed to 46 °C for the entire protein; , for EF-1α, the catalytic subunit loses activity at 84 °C and the entire protein at 94 °C .…”
Section: Introductionmentioning
confidence: 99%
“…The cooperative participation of all three EF-Tu domains is necessary to ensure a phenotype regarding the binding of guanine nucleotides both in T. thermophilus [10] and E. coli [11]. While, for example, high affinity for GDP and GTP is an inherent property of the G-domain in EF-Tu from Bacillus stearothermophilus [12], and partial truncation of Sulfolobus solfataricus EF-1α increases the binding affinity of GDP and GTP by approximately one order of magnitude compared to intact protein [13]. Mutational analysis of catalytic His84 in E. coli EF-Tu and homologous His85 in T. thermophilus EF-Tu revealed similar mechanisms of GTP hydrolysis by these two proteins [14][15][16].…”
Section: Introductionmentioning
confidence: 99%